Multidisciplinary treatment of giant chondrosarcoma of the proximal femur by external hemipelvectomy and reconstruction with a pedunculated Fillet flap: presentation of a clinical - Stoppiello, Pablo; Casales, Nicolás; Silveri, Claudio; Bianchi, Gottardo; Gaiero, Leticia; Wolf, Daniel; Diamant, Marcelo; Pintos, Fabricio; Rey, Rogelio; Francescoli, Luis (Cirugía del Uruguay, 2022)
Chondrosarcoma is one of the most frequent malignant primary tumors. Pelvic and proximal femur locations require extensive approaches with the consequent difficulty of soft tissue reconstruction. External hemipelvectomy is usually the procedure for these locations. It involves total en bloc resection of the lower extremity associated with ipsilateral hemipelvis, resulting in a large coverage defect. In some cases, local rotational flaps are impossible. Reconstruction with fillet flaps offers an adequate coverage for soft tissue defects. The objective of this study is to show the resolution of an unconventional case of chondrosarcoma of the proximal femur and its soft tissue reconstruction with a method never before used in our country.